Seasonal distribution of organic carbon in the surface sediments of the Terengganu nearshore coastal area - Shaari, Hasrizal; Yunus, Kamaruzzaman; Ibrahim, Sakri; Ong, Meng Chuan; Mohamad Shazili, Noor Azhar (Science Publications, 2009)
Terengganu water experienced the semi annual reversal in the wind system and the reversal in the current flow, in the upper layer of the ocean. Due to this reason, a north east monsoon season and a south east monsoon season, can be clearly distinguished in the South China Sea. Their coastal near shore areas are active sites where huge amount of organic matter is introduced into the ocean system through river runoff, in situ primary production and anthropogenic impacts. Interaction between a complex mixture of organics and inorganic enhances active material cycling's in time and space. However, different factors may control the partitioning and also the bioavailability of the hydrophobic organic compound pollutants within the benthic ecosystem. These factors include various sediment characteristics, such as grain size distribution, mineral composition and organic content (1), (2), (3). Surface sediments may be resuspended and redistributed by the action of waves and currents (4), (5). As these phenomena erode the top most layers of the sediment column, resuspended sediments contain recently deposited organic matter. In shallow water bodies of about a few meters deep, this matter may be rich in easily degradable fractions, as debris from dead marine organisms may rapidly settle onto the sediment surface. Therefore, through the processes of sediment resuspension and redistribution, organic matter at the sediment-water interface may be a significant source of easily remineralizable materials.